The Regional Jus Cogens: A Paradox in International Law? (De Legibus - Law Journal, 2025)
In this paper, we will explore the concept of regional jus cogens, attempting to discern if its existence is possible and under what terms. Initially, we will delve into the notion and characteristics of jus cogens norms. Later, we will discuss the stance of various authors and states regarding the possibility of this institute’s existence. We will also examine the various problems and consequences that this concept raises. Then, I will present to you a landmark case on this topic and discuss Brezhnev’s doctrine. Finally, I will outline the position I take and a potential normative alternative.
Keywords: regional jus cogens; peremptory norms; non-derogable norms; international law.